ANALYSIS OF FAMILY NURSING WITH THE APPLICATION OF MUSIC THERAPY TO SCHIZOPHRENIA CLIENTS TO OVERCOME DISORDER OF SENSORY PERCEPTION - Efendi, Yumita; Setiyowati, Eppy; Rusdianingseh; Zahroh, Chilyatiz (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Auditory hallucinations are a common sensory perception disorder affecting approximately 70% of individuals diagnosed with schizophrenia. Various factors contribute to hallucinations, including physical, emotional, intellectual, social, and spiritual dimensions. Objective: This study aims to evaluate the effectiveness of music therapy in mitigating sensory perception disorders in individuals with schizophrenia. Methods: A descriptive case study approach was employed. Data were collected through interviews, observations, and physical examinations involving clients and their families. The Standard Operating Procedure (SOP) for Classical Music Therapy was utilized. The study focused on a single individual experiencing auditory hallucinations within a family setting. Results: Implementing music therapy over four days (one session per day, approximately 13 minutes) resulted in reduced auditory disturbances, decreased anxiety, improved sleep quality, and a decline in the Auditory Hallucination Rating Scale (AHRS) score from 24 to 11, along with a reduction in the Hamilton Rating Scale for Anxiety (HRS-A) score from 26 to 12. Conclusions: Classical music therapy effectively reduces auditory hallucinations and alleviates anxiety in individuals with schizophrenia. Therefore, it is recommended as a non-pharmacological intervention and an independent nursing practice for managing sensory perception disorders.